The Development of Core Competencies in Active Citizens with Global Mindedness for Teaching Professional Experience Training Students with a Context-Based Massive Open Online Course Activity Pack Integrate Coaching and Mentoring - Potisart, Janesuk; Prachopchok, Prathan; Supprakob, Surayot; Dokmai, Patcha; Duangmanee, Daojai (SOCIAL SCIENCES RESEARCH AND ACADEMIC JOURNAL, 2025)
This research and development study aimed to: 1) develop and validate the effectiveness of a context-based Massive Open Online Course (MOOCs) activity package integrated with coaching and mentoring for pre-service teachers; 2) evaluate the effectiveness index of the activity package; and 3) assess the development of core competencies in active citizenship with global mindedness. Using a mixed-method research design, the study involved 150 fourth and fifth-year pre-service teachers. The findings revealed that the activity package comprised an introductory module and five main modules: 1) Rights-Respecting Citizens, 2) Responsible Citizens, 3) Critical-Thinking Citizens, 4) Participatory Citizens, and 5) Change Agent Citizens. The package’s content validity was validated by 10 experts and 10 researchers, yielding a highly appropriate rating (M = 4.92). The efficiency value (E1/E2) was 72.63/75.44, meeting the predetermined criteria. The effectiveness index was 0.3148, indicating a 31.48% improvement in students’ core competencies across all three groups. Analysis of competency development showed statistically significant improvements (p < .05) in experimental groups 1 and 2 compared to their pre-test scores, while the control group (group 3) showed no significant change. Significant differences were observed between experimental group 1 versus control group 3, and experimental group 2 versus control group 3 (p < .05) Behavioral outcomes and learning reactions in groups 1 and 2 progressed from the "active citizen" level to the "change agent" level, with an overall mean score of 4.35 for reactions and learning. The control group maintained their initial "active citizen" level without significant change.